Mn deposition/dissolution chemistry and its contemporary application in R&D of aqueous batteries - Soundharrajan, Vaiyapuri; Nithiananth, Subramanian; Muthukrishnan, Akshaiya Padmalatha; Singh, Gita; Arifiadi, Anindityo; Tung, Duong Pham; Kim, Jung Ho; Kim, Jaekook (Frontiers in Batteries and Electrochemistry, 2024)
The advancement of Mn deposition/dissolution chemistry and its translation to different battery variants is progressively documented. However, Mn represents poor reversibility, causing limitations for practical application. With the purpose of improving Mn-based battery operation, various technical solutions have been implemented for numerous batteries with Mn deposition/dissolution chemistry. This review summarizes the rapid advancements on Mn deposition/dissolution chemistry-based aqueous batteries.